SEASONAL VARIATION OF IN SITU PHYTOPLANKTON PHOTOSYNTHETIC PROPERTIES IN NHA TRANG BAY - Thi Minh Hue Tran; Nhu Hai Doan (Tạp chí Khoa học Đại học Đà Lạt)
Photosynthetic properties are essential for the evaluation of phytoplankton photosynthetic efficiency as well as their physiological status in different waters. The present study measured in situ minimum and maximum fluorescence (Fo, Fm), variable fluorescence (Fv), and photosynthetic efficiency (Fv/Fm) in Nha Trang Bay to estimate seasonal phytoplankton community responses to different environmental conditions. Photosynthetic efficiency of in situ phytoplankton in Nha Trang Bay varied from 0.03 to 0.55 among stations and sampling times. Stations near the shore (Cape Chut) and estuary had higher Fv/Fm values than offshore stations. Seasonal and spatial variation of photosynthetic efficiency along the transect from the river mouth to the open ocean reflected the impact of river inputs on phytoplankton communities. In situ measurements indicate the impacts of complex environmental conditions in Nha Trang Bay (e.g., light intensity and nutrients) on the physiological status and photosynthetic efficiency of phytoplankton.